Hygro-thermo-mechanical performance of wheelchair cushion technologies in the prevention of pressure ulcers and moisture-associated skin damages - Bogard, Fabien; Polidori, Guillaume; Murer, Sébastien; Maalouf, Chadi; Blancheteau, Yannick; Quinart, Hervé; Beaumont, Fabien (Assistive Technology, 2023)
This study aims at investigating the effects of three different wheelchair cushion technologies at the patient–wheelchair interface. To this end, eight participants were recruited to remain in an unrelieved seated position on a wheelchair successively equipped with three different cushions (foam, air-cell-based and gel), for a duration of 45 min. Interface pressure, temperature (measured with infrared thermography) and relative humidity were measured at the seat interface, at different timestamps. Experimental results show that foam cushion is significantly more efficient in reducing contact peak pressure (p < .01), while the gel cushion displays higher heat evacuation capabilities. In terms of relative humidity, no significant difference is observed among the three technologies (p > .29): all of them evacuate around only 10% of the total humidity compared to the reference situation (i.e., without cushion). Besides, a complementary numerical simulation corresponding to the steady state of the patient-wheelchair structure clearly highlights the temperature volume field at the underside of the seat, which acts like a thermal barrier and contributes to heat accumulation. Besides, an air flow at the underside of the chair in motion is shown to significantly reduce heat accumulation.
Keywords: MASD; heat dissipation; infrared thermography; numerical simulation; pressure peaks; relative humidity